A computer game in the simulator genre using unity - Vrakina, K. P.; Vrakina, V. V. (My University, 2022)
Nowadays, video games are gaining popularity and development, in particular, the genre of incremental games is very relevant. It is gaining popularity in the mobile gaming market and dominates many flash portals, solving many revenue management tasks, focusing on making decisions that increase revenue.
Keywords: development; mobile game; idle game; clicker; encryption; Unity